Broad-Based Black Economic Empowerment in selected Small and Medium Enterprises in Cape Town, South Africa - Cader, Abraham Alexander; Mazhazha-Nyandoro, Zivanayi (The journal of contemporary issues in business and government, 2023)
The implementation of the Black Economic Empowerment (BEE) legislation in 2003 amended to Broad-Based Black Economic Empowerment (thereafter, BBBEE) has indicated that not much has changed over the years. The qualitative research approach adopted an exploratory case study design to explore the perceptions of SMEs owners and managers in Cape Town, South Africa. The study findings indicate that the legislation has been a hindrance and has failed to address the social injustices of the past. Findings indicate lack access to opportunities in the public sector, ‘fronting’ by the connected elites, fraud, corruption. The main conclusions are that the legislation has failed to level the playing field for SMEs owned by the previously disadvantaged individuals (PDIs). The study recommendations are that legislation should be overhauled and re-purposed to deliver the economic empowerment of the previously disadvantaged individuals and communities in South Africa.